(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
The aim of this article is to examine the conceptualization of the auditory dimension of war experience in recent poetry by Polish and Ukrainian women poets. This dimension is characterized by complexity, pervasive transformation and an increase in the intensity and volume of sounds. The analysis focuses on identifying the emergence of new and/or redefined standard sounds, on characterizing the invalidation and/or invention of previously unknown auditory practices, with their traumatic inflection. This wartime hearing/listening is dominated by loss, a sense of threat, fear and the proximity of death. The studied corpus includes contemporary poems by Polish women poets (Maria Pawlikowska-Jasnorzewska, Anna Świrszczyńska) and the most recent works by Ukrainian women poets published between 2022 and 2024. The latter includes four bilingual volumes from the Ukrainian Poetry Library series titled In the Face of War as well as the monologue poem by Yaryna Chornohuz, published outside the series.